A new direction in the pathogenesis of idiopathic pulmonary fibrosis? - Gauldie, Jack (BioMed Central, 2002)
A recent review article suggested that idiopathic pulmonary fibrosis (IPF) is a disease that is associated more with abnormal wound healing than with inflammation. Data derived from transgenic and gene transfer rodent models suggest that lung inflammation may be a necessary but insufficient component of IPF, and that at some point in the natural history of the disease IPF becomes no longer dependent on the inflammatory response for propagation. Altered microenvironment and involvement of epithelial cell/mesenchymal cell interaction are the most likely contributors to the pathogenesis of this chronic progressive disorder.